The Nose and the Lung: United Airway Disease? - Licari, Amelia; Castagnoli, Riccardo; Denicolò, Chiara Francesca; Rossini, Linda; Marseglia, Alessia; Marseglia, Gian Luigi (Frontiers in Pediatrics, 2017)
Epidemiologic, pathophysiological and clinical evidence recently revealed the link between upper and lower airways, changing the global pathogenic view of respiratory allergy. The aim of this review is to highlight the strong interaction between the upper and lower respiratory tract diseases, in particular allergic rhinitis and asthma.